BABY SCREEN TIME FROM AN ISLAMIC GUIDANCE PERSPECTIVE: A CASE STUDY OF PARENTS' EXPERIENCES IN SHOWING SHORT VIDEOS TO YOUNG CHILDREN - Kholidin, Farid Imam; Zahara, Penisa Bunga (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to understand the dynamics of early childhood care in farming families in Koto Rendah Village, with an emphasis on parental communication patterns, Islamic parenting approaches, and the influence of digital device use on child development. Using a qualitative case study approach, this study involved several families as key participants. Data were collected through in-depth interviews and observations, then analyzed using thematic techniques to identify patterns of meaning that emerged from the participants' experiences. The results of the study show that limited interaction between parents and children has an impact on weak digital supervision, especially in a limited socioeconomic context. However, Islamic parenting values such as role modeling, compassion, and trust-based communication can serve as a strong foundation for shaping children's character and preventing the negative impacts of technology. This study highlights the importance of improving digital parenting literacy integrated with Islamic values and the strategic role of Islamic education counselors in providing family spirituality-based guidance. Conceptually, this study enriches the study of Islamic education and family counseling in the digital age. Practically, these findings are relevant for the development of parent assistance programs, mosque-based interventions, and values-based child education policies. This study also opens up broader exploration to understand the challenges of digital parenting in different cultural and economic contexts.